The susceptibility of pathogens associated with acne vulgaris to antibiotics (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND Acne vulgaris is a pilosebaceous disorder. Bacterial activity and inflammation both influence acne formation. Antibiotics suppress the bacterial activities and elicit anti-inflammatory effects. The overuse of antibiotics may lead to resistance in bacteria. This study was aimed to provide an overview of bacteria that may cause acne and determine their susceptibility to antibiotics. METHODS This was a cross-sectional study sampling from 93 patients with acne in Ciptomangunkusumo Hospital. Comedones were extracted and cultured on Brucella blood agar, under aerobic and anaerobic conditions at 35oC for 24–48 hours. Bacterial identification was performed using Vitek®, and susceptibility test using E-test. Data interpretation was based on the Clinical and Laboratory Standards Institute 2015. RESULTS Staphylococcus epidermidis (50.5%), Propionibacterium acnes (11.0%), and Staphylococcus aureus (7.7%) were identified. Bacteria were not found in 69.2% and 1.1% of samples in anaerobic and aerobic cultures, respectively. P. acnes was susceptible to doxycycline (100%) and minocycline (100%), while 10% was resistant to erythromycin, clindamycin, and tetracycline. S. epidermidis was susceptible to minocycline (100%); but resistant to erythromycin (65.2%), clindamycin (52.2%) and tetracycline (32.6%). The susceptibility of S. epidermidis to doxycycline was 89.1%, which was lower than that of P. acnes (100%). S. aureus was found to be sensitive to minocycline (100%), doxycycline (71.4%), clindamycin (71.4%), and tetracycline (71.4%); but it was resistant to erythromycin (42.9%). CONCLUSIONS Doxycycline and minocycline showed 100% effectiveness for P. acnes. The isolated bacteria were more susceptible to doxycycline compared to tetracycline. The use of clindamycin and erythromycin needs to be limited as most S. epidermidis isolates were resistant to both.